1983
DOI: 10.2135/cropsci1983.0011183x002300020025x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Selection for Nectar Volume, Receptacle Diameter, and Seed Yield Characteristics in Alfalfa1

Abstract: California produces more than 30% of the US alfalfa (Medicago sativa L.) seed crop. The majority of this seed is produced using honey bees (Apis mellifera) for pollination. Strength of reward, i.e. quantity and quality of nectar, is a primary factor in pollinator foraging activity. Positive correlations occur between nectar production and honey bee visitation, and honey bee visitation and seed production. Objectives of this investigation were to determine the effectiveness of phenotypic recurrent selection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Along with foraging distance, the number of individual flowers visited and the spatial scale of the visits by a bee on any given foraging trip will dictate the degree of gene flow between RR and conventional alfalfa (Pedersen 1953; Teuber et al 1983; Cane 2002). Also, an alfalfa flower must be tripped in order to be successfully pollinated.…”
Section: Discussionmentioning
confidence: 99%
“…Along with foraging distance, the number of individual flowers visited and the spatial scale of the visits by a bee on any given foraging trip will dictate the degree of gene flow between RR and conventional alfalfa (Pedersen 1953; Teuber et al 1983; Cane 2002). Also, an alfalfa flower must be tripped in order to be successfully pollinated.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent selection in soybean with male-sterile, female-fertile mutants was reviewed by Lewers and Palmer (1997). These genetic differences in soybean should be amenable to plant breeding manipulation similar to what has been with alfalfa (Teuber et al 1983(Teuber et al , 1990.…”
Section: Reward: Pollen and Nectarmentioning
confidence: 99%
“…There is evidence that nectar production in some species is, to some degree, heritable (Pedersen 1953, Hawkins 1971, Teuber & Barnes 1979, Teuber et al 1983, Mitchell & Shaw 1993, Campbell 1996, Mitchell et al 1998, Golubov et al 1999). Other studies have not used genetic methods but have shown that individuals have consistent nectar phenotypes, sometimes across seasons (Pleasants 1983, Zimmerman & Pyke 1986, Hodges 1993.…”
Section: For Alljowers Sampled At Noon For Any Aspect Of This Projectmentioning
confidence: 99%